Comparison of a multiplex-PCR assay with mycolic acids analysis and conventional methods for the identification of Mycobacteria - Tanaka, Ioshie Ibara; Anno, Ivone Shizuko [UNESP]; De Andrade Leite, Sergio Roberto [UNESP]; Cooksey, Robert C.; Leite, Clarice Queico Fujimura [UNESP] (Wiley, 2003)
A fast, sensitive and cost-effective multiplex-PCR assay for Mycobacterium tuberculosis complex (MTC) and Mycobacterium avium (M. avium) identification for routine diagnosis was evaluated. A total of 158 isolates of mycobacteria from 448 clinical specimens from patients with symptoms of mycobacterial disease were analyzed. By conventional biochemical methods 151 isolates were identified as M. tuberculosis, five as M. avium and two as Mycobacterium chelonae (M. chelonae). Mycolic acid patterns confirmed these results. Multiplex-PCR detected only IS6110 in isolates identified as MTC, and IS1245 was found only in the M. avium isolates. The method applied to isolates from two patients, identified by conventional methods and mycolic acid analysis, one as M. avium and other as M. chelonae, resulted positive for IS6110, suggesting co-infection with M. tuberculosis. These patients were successfully submitted to tuberculosis treatment. The multiplex-PCR method may offer expeditious identification of MTC and M. avium, which may minimize risks for active transmission of these organisms and provide useful treatment information.
Keywords: Classical procedures for identification; Multiplex-PCR; Mycobacterium avium; Mycobacterium chelonae; Mycobacterium tuberculosis; Mycolic acids analysis; mycolic acid; bacterial transmission; bacterium identification; cost effectiveness analysis; Mycobacterium; Mycobacterium chelonei; nonhuman; polymerase chain reaction; Bacterial Typing Techniques; DNA Transposable Elements; DNA, Bacterial; Humans; Mycobacterium avium Complex; Mycobacterium Infections; Mycolic Acids; Polymerase Chain Reaction; Sensitivity and Specificity; Actinobacteria (class); Bacteria (microorganisms); Corynebacterineae; uncultured actinomycete